What Should a Congregation Sing?: A Few Thoughts on Hymnology - Scheide, William H. (Theology today, 1963)
EDITOR'S NOTE: This essay was originally prepared in connection with the Sesquicentennial celebrations of Princeton Theological Seminary. As the article indicates, the point of departure is Louis FitzGerald Benson, a graduate of Princeton Seminary in the class of 1887 and a collector of hymnbooks and writer in the field of hymnology. It was felt that this discussion should be published in THEOLOGY TODAY where its vigorous thesis, as well as its equally vigorous strictures on the kind of hymnody Benson represented, could be read and studied by the widest possible audience. It will be clear that the main point of the article is not Benson but the plight of contemporary church music, especially congregational singing.